ANALISIS PERILAKU DISRUPTIF SISWA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS V DI SEKOLAH DASAR NEGERI SEPULU 1 - Atiyah; Abdussalam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze disruptive behavior in fifth-grade Indonesian language learning at SDN Sepulu 1. The research method used is qualitative with a case study approach through observation, interviews, and documentation. The results of the study indicate that the forms of disruptive behavior that appear include talking without permission, disturbing friends, not doing assignments, entering and leaving the class without permission, and making distracting sounds or movements. Factors that influence this behavior consist of internal factors (lack of self-control, low interest in learning, and the need for attention), external factors (less varied learning methods, teacher assertiveness, and peer influence), and family factors (minimal supervision and inappropriate parenting). Teacher strategies in dealing with disruptive behavior include the application of consistent class rules, direct reprimands, personal approaches, positive reinforcement, the use of varied learning methods, and cooperation with parents. This study concludes that disruptive behavior is the result of the interaction of various factors, but can be minimized through appropriate learning strategies and collaboration between teachers and parents, thereby creating a conducive learning environment and supporting the development of positive student behavior.